FEATURES OF THE APPLICATION OF THE MODERN METHOD OF APA (EDUCATION IN THE 21ST CENTURY, 2023)
In the article entitled "Features of application of modern method APA - training" we tried to show a kind of layers application of the method, due to the nature of the learner material, the need for its in-depth analysis, interlinked with the interpretation of previous material and new teaching topics. The features of the application of this method became more visible and understandable based on the analysis of the story "Lar-Margar" by .Ak.Bakunts The main objective of the study is to identify features of application of modern method of APA- - learning, the advantages of the method as an interesting learning through a deeper interpretation of the material, systematization and generalization of previous material, explanation of new material with the previous topic, thorough analysis of the subject and strengthen the acquired knowledge. In the methodological literature, there are a number of scientific studies devoted to the above problem: "Modern methods of teaching, techniques, exercises", Lori Department of the KAI, with Vanadzor, 2008, S. Sarukhanyan, Dr. I., Modern methods, techniques, exercises, Yerevan 2009, "effective teaching techniques", S. Khachatryan, E. F. Ebert Foundation, Armenia, 2020, Valmont In "Technologies for literacy and learning". New York. Houghton Mifflin Company, 20 The above-mentioned authors tried to present the features inherent in modern teaching methods and the features of their application in their own way.162The purpose of the article is to identify the essence of the above method, the principles of teaching material by this method, indicating and justifying its advantages due to the relevant features of this method of teaching, as well as the features arising from the purpose of teaching. The novelty of this study is the consideration of the phased application of the modern method of APA - training. The article considers the relationship between the artistic material and the historical period as a means of in-depth analysis of the learning material.
Keywords: Stimulation, perception of meaning, reasoning, ideological problems, artistic value, means of icon painting.